Pengaruh Pengetahuan Keuangan, Sikap Keuangan, dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan Pada Pasangan Menikah Muda - Sholikhah, Oktaviani Maratush; Purnamawati, Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This research discusses this problem regarding financial management behavior in young married couples. The purpose of this study was to determine the effect of financial knowledge, financial attitudes, and lifestyle on financial management behavior partially or simultaneously. The research method used is quantitative. The analysis used is Multiple Linear Regression Analysis, Classical Assumption Test, Hypothesis Test, and Coefficient of Determination Test. The results of this study are (1) Financial knowledge partially has a positive and significant effect on financial management behavior in young married couples (2) Financial attitudes partially have a positive and significant effect on financial management behavior in young married couples (3) Lifestyle partially has a negative and significant effect on financial management behavior in young married couples (4) Financial knowledge, financial attitude and lifestyle simultaneously have a positive and significant effect on financial management behavior in young married couple.